Cognitive Neural Mechanism of Backward Inhibition and Deinhibition: A Review - Chen, Jiwen; Wu, Shujie; Li, Fuhong (Frontiers in Behavioral Neuroscience, 2022)
Task switching is one of the typical paradigms to study cognitive control. When switching back to a recently inhibited task (e.g., “A” in an ABA sequence), the performance is often worse compared to a task without N-2 task repetitions (e.g., CBA). This difference is called the backward inhibitory effect (BI effect), which reflects the process of overcoming residual inhibition from a recently performed task (i.e., deinhibition). The neural mechanism of backward inhibition and deinhibition has received a lot of attention in the past decade. Multiple brain regions, including the frontal lobe, parietal, basal ganglia, and cerebellum, are activated during deinhibition. The event-related potentials (ERP) studies have shown that deinhibition process is reflected in the P1/N1 and P3 components, which might be related to early attention control, context updating, and response selection, respectively. Future research can use a variety of new paradigms to separate the neural mechanisms of BI and deinhibition.